Dermal Uptake of 18 Dilute Aqueous Chemicals: In Vivo Disappearance‐Method Measures Greatly Exceed In Vitro‐Based Predictions. Issue 7 (10th October 2012) - Bogen, Kenneth T.
<x xml:space="preserve">Abstract</x> Average rates of total dermal uptake (Kup) from short‐term (e.g., bathing) contact with dilute aqueous organic chemicals (DAOCs) are typically estimated from steady‐state in vitro diffusion‐cell measures of chemical permeability (Kp) through skin into receptor solution. Widely used ("PCR‐vitro") methods estimate Kup by applying diffusion theory to increase Kp predictions made by a physico‐chemical regression (PCR) model that was fit to a large set of Kp measures. Here, Kup predictions for 18 DAOCs made by three PCR‐vitro models (EPA, NIOSH, and MH) were compared to previous in vivo measures obtained by methods unlikely to underestimate Kup. A new PCR model fit to all 18 measures is accurate to within approximately threefold (r = 0.91, p < 10−5), but the PCR‐vitro predictions (r > 0.63) all tend to underestimate the Kup measures by mean factors (UF, and p value for testing UF = 1) of 10 (EPA, p < 10−6), 11 (NIOSH, p < 10−8), and 6.2 (MH, p = 0.018). For all three PCR‐vitro models, log(UF) correlates negatively with molecular weight (r2 = 0.31 to 0.84, p = 0.017 to < 10−6) but not with log(vapor pressure) as an additional predictor (p > 0.05), so vapor pressure appears not to explain the significant in vivo/PCR‐vitro discrepancy. Until this discrepancy is explained, careful in vivo measures of Kup should be obtained for more chemicals, the expanded in vivo database should be compared to in vitro‐based predictions, and in vivo data should be considered in assessing aqueous dermal exposure and its uncertainty.